Sawtooth multi-ring electrodes for ionic wind propulsion - Miaosen Hou; Jifan Zhang; Ronghui Quan (Scientific Reports)
Abstract Recently, the application of ionic wind in atmospheric propulsion has gained significant attention, but existing devices face challenges in achieving sufficient thrust for practical applications. This study proposes a novel electrode structure combining a serrated single-ring emitter and multi-ring collector, which offers two key advantages: (1) The 1–2 times thrust increase is achieved through enhanced ion generation, improved ion drift efficiency, enabled by the sawtooth emitter and multi-ring collector design, (2) a compact, lightweight (17 g) design with good structural stability. We compared three electrode structures under varying conditions (voltage: 20–40 kV, electrode gaps: 60–120 mm, ring diameters: 60–100 mm). The sawtooth multi-ring structure achieved a maximum thrust of 164 mN/m under 40 kV and a 60 mm gap. Furthermore, through further optimization of the structural parameters of the sawtooth multi-ring, the thrust density achieved a 28.2% enhancement under equivalent operational conditions. This result highlight the potential of ionic wind propulsion for low-altitude flight, with further optimization promising greater efficiency.